Social variables affecting the demographic waste of a young category Age of less than 15 years in the Diwaniyah and Afak - AL-Khazraji, Raad Mufeed Ahmed; Albedairy, Fuad Kadhim Najim (Al-Adab Journal, 2023)
The young age group is the backbone of any society, and because of its importance it has received great attention from international, governmental and societal institutions, to develop, develop and protect them from aggression, deviation, exploitation, backwardness and loss, but all these measures did not prevent a demographic waste of this category. The research aims to identify the size of the waste of the young category in the Diwaniyah and Afak, and to reveal the social variables affecting its distribution and spatial variation, in order to develop a future vision for the young category and expectations of the size of waste and its indicators, and to achieve this was the use of the descriptive and analytical approach and the quantitative style, and it was tab Data in statistical schedules turned into rates and relative importance to compare them at the level of administrative units and the use of maps and graphs for the same purpose, with the use of the standard degree to clarify the economic variables affecting the phenomenon of demographic waste and visually compare them with the size of the total waste to reach spatial relationships related to the power of the size of the waste, and the research was approved In its data on the data of the Ministry of Planning, the Central Agency for Statistics and Technology Information, and the data of the Ministry of Education (Al -Qadisiyah Education Directorate), the data of the Ministry of Justice and Social Affairs and the Ministry of Health and Environment (Diwaniyah Health Department), and the data of the Ministry of Interior (Qadisiyah Police, Juvenile Department), the Ministry of Justice and the Supreme Council and the courts (Diwaniyah, Sunni, Al -Daghara, Afak, Al -Badir, Sumer) for the year 2020 and field study for the year 2021. The waste rate for the year 2020 (78.16) children per thousand people, and it is noted that there is a spatial contrast at the level of administrative units in the waste rates, as the Shafi’i Nahiya came with the highest rate of (93.55), and the Badir district came with the lowest rate (48.45).